Switching regimens in virologically suppressed HIV‐1‐infected patients: evidence base and rationale for integrase strand transfer inhibitor (INSTI)‐containing regimens. (October 2016) - Raffi, F; Esser, S; Nunnari, G; Pérez‐Valero, I; Waters, L
Abstract : In an era when most individuals with treated HIV infection can expect to live into old age, clinicians should proactively review their patients' current and future treatment needs and challenges. Clinical guidelines acknowledge that, in the setting of virological suppression, treatment switch may yield benefits in terms of tolerability, regimen simplification, adherence, convenience and long‐term health considerations, particularly in the context of ageing. In this paper, we review evidence from six key clinical studies on switching virologically suppressed patients to regimens based on integrase strand transfer inhibitors (INSTIs), the antiretroviral class increasingly preferred as initial therapy in clinical guidelines. We review these studies and focus on the virological efficacy, safety, and tolerability of switching to INSTI‐based regimens in suppressed HIV‐positive individuals. We review the early switch studies SWITCHMRK and SPIRAL [assessing a switch from a ritonavir‐boosted protease inhibitor (PI/r) to raltegravir (RAL)‐containing regimens], together with data from STRATEGY‐PI [assessing a switch to elvitegravir (EVG)‐containing regimens; EVG/cobicistat (COBI)/emtricitabine (FTC)/tenofovir disoproxil fumarate (TDF) vs . remaining on a PI/r‐containing regimen], STRATEGY‐NNRTI [assessing a switch to EVG/COBI/FTC/TDF vs . continuation of a nonnucleoside reverse transcriptase inhibitor (NNRTI) and two nucleoside reverse transcriptase inhibitors (NRTIs)], STRIIVING [assessing a switch to a dolutegravir (DTG)‐containing regimen (abacavir (ABC)/lamivudine (3TC)/DTG) vs . staying on the background regimen], and GS study 109 [assessing a switch to EVG/COBI/FTC/tenofovir alafenamide fumarate (TAF) vs . continuation of FTC/TDF‐based regimens]. Switching to INSTI‐containing regimens has been shown to support good virological efficacy, with evidence from two studies demonstrating superior virological efficacy for a switch to EVG‐containing regimens. In addition, switching to INSTI regimens was associated with improved tolerability and greater reported patient satisfaction and outcomes in some studies. INSTI‐based regimens offer an important contemporary switch option that may be tailored to meet and optimize the needs of many patients.